Development of a Novel Hematological Malignancy Specific Patient-Reported Outcome Measure (HM-PRO): Content Validity - Goswami, Pushpendra; Oliva, Esther N.; Ionova, Tatyana; Else, Roger; Kell, Jonathan; Fielding, Adele K.; Jennings, Daniel M.; Karakantza, Marina; Al-Ismail, Saad; Collins, Graham P.; McConnell, Stewart; Langton, Catherine; et al. (Frontiers in Pharmacology, 2020)
Background: The quality of life of patients at all stages of haematological malignancy is greatly affected by disease and its treatment. There is wide range of health-related quality of life (HRQoL) issues important to these patients. Any new instrument developed to measure HRQoL of such patients should be content valid, i.e. items should be comprehensively relevant to the patients and their health condition. The aim of the present study was to examine content validity of a haematological malignancy specific patient reported outcome measure (HM-PRO) developed for use in routine clinical practice. Methods: Following literature review and semi-structured interviews, the generated themes and sub-themes were discussed to develop the prototype version of the HM-PRO. A 4-step approach was used for content validation: initial testing and cognitive interviewing; item rating; content validity panel meeting; final field testing and cognitive interviewing. Additional questions related to patients’ perception of recall period and preferred sentence structure (i.e.question or statement) of items were also asked during cognitive interviews. Results: The content analysis of 129 transcribed semi-structured interviews resulted in the prototype version of instrument consisting of 58 items grouped into two parts: Part A (impact/HRQoL-34 items) and Part B (signs & symptoms–24 items). The initial testing showed intraclass correlation coefficient (ICC) of >0.8 for both Part A and Part B. Item rating for language clarity, completeness, relevance, and response scale by experts and patients showed content validity index for scales average>0.8 for both Part A and Part B, except 0.64 for relevance for Part A by the patient panel. The final testing of revised version of instrument showed the Cronbach’s alpha value of 0.91 for Part A and 0.76 for Part B,suggesting high internal consistency, and ICC of 0.91 for Part A and 0.76 for Part B. The recall period of ‘today’ for Part-A and ‘last 3 days’ for Part-B were the patients’ preferred ‘recall period’. Furthermore, patients expressed preference to HM-PRO items as statements. Conclusion: The findings of this study confirm that the HM-PRO possesses a strong content validity, includes all issues important to patients and is easy to read, understand and respond to spontaneously.